ANALISIS FAKTOR YANG MEMPENGARUHI GREEN PURCHASE INTENTION DIMODERASI OLEH GREEN BRAND KNOWLEDGE - Elistia, Elistia; Rohmatin, Sartika Dwi (Universitas Indraprasta PGRI Jakarta, 2024)
Environmental issues have become a serious concern for marketers, when the amount of waste continues to increase and is difficult to recycle. This study aims to analyze the factors that influence green purchase intention moderated by green brand knowledge. This study uses a quantitative approach with a descriptive causality method. The population in this study were consumers who were interested in buying environmentally friendly products of the Tupperware brand. The sampling method used non-probability sampling through purposive sampling techniques with a total of 152 respondents analyzed using SEM-PLS. The results showed that Attitude, Subjective Norm, Perceived Behavioral Control, Green Brand Positioning and Green Brand Knowledge had a positive effect on Green Purchase Intention. However, green brand knowledge which is a moderating variable shows that it does not have a moderating effect on the relationship between Attitude, Subjective Norm, Perceived Behavioral Control and Green Purchase Intention. The findings of this study indicate that Green Brand Knowledge has a moderating effect, but weakens the relationship between Green Brand Positioning and Green Purchase Intention.